Prolonged Low-Dose Methylprednisolone in Patients With Severe COVID-19 Pneumonia. (12th September 2020) - Salton, Francesco; Confalonieri, Paola; Meduri, G Umberto; Santus, Pierachille; Harari, Sergio; Scala, Raffaele; Lanini, Simone; Vertui, Valentina; Oggionni, Tiberio; Caminati, Antonella; Patruno, Vincenzo; Tamburrini, Mario; et al.
Abstract: Background: In hospitalized patients with coronavirus disease 2019 (COVID-19) pneumonia, progression to acute respiratory failure requiring invasive mechanical ventilation (MV) is associated with significant morbidity and mortality. Severe dysregulated systemic inflammation is the putative mechanism. We hypothesize that early prolonged methylprednisolone (MP) treatment could accelerate disease resolution, decreasing the need for intensive care unit (ICU) admission and mortality. Methods: We conducted a multicenter observational study to explore the association between exposure to prolonged, low-dose MP treatment and need for ICU referral, intubation, or death within 28 days (composite primary end point) in patients with severe COVID-19 pneumonia admitted to Italian respiratory high-dependency units. Secondary outcomes were invasive MV-free days and changes in C-reactive protein (CRP) levels. Results: Findings are reported as MP (n = 83) vs control (n = 90). The composite primary end point was met by 19 vs 40 (adjusted hazard ratio [aHR], 0.41; 95% CI, 0.24–0.72). Transfer to ICU and invasive MV were necessary in 15 vs 27 ( P  = .07) and 14 vs 26 ( P  = .10), respectively. By day 28, the MP group had fewer deaths (6 vs 21; aHR, 0.29; 95% CI, 0.12–0.73) and more days off invasive MV (24.0 ± 9.0 vs 17.5 ± 12.8; P  = .001). Study treatment was associated with rapid improvement in PaO2 :FiO2 and CRP levels. The complication rate was similar for the 2 groups ( P  = .84). Conclusion: In patients with severe COVID-19 pneumonia, early administration of prolonged, low dose MP treatment was associated with a significantly lower hazard of death (71%) and decreased ventilator dependence. Treatment was safe and did not impact viral clearance. A large randomized controlled trial (RECOVERY trial) has been performed that validates these findings. Clinical trial registration.  ClinicalTrials.gov NCT04323592. Abstract : This multicenter observational study gave the first evidence that prolonged, low-dose methylprednisolone treatment is associated with a significantly lower hazard of death, reduced ICU burden and decreased ventilator dependence without affecting viral clearance in patients with severe COVID-19 pneumonia/ARDS.